Acceptability and feasibility of immediate postpartum IUCD insertion in a tertiary care centre in Central India - Kanhere, Anjali Vivek; Pateriya, Prachi; Jain, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was conducted to assess the acceptability and feasibility of immediate postpartum intrauterine contraception device insertion after vaginal deliveries in a tertiary care centre in Central India. Aims: To study acceptability, feasibility & complications of immediate PPIUCD. Methods: This is a prospective analytical study conducted at Department of Obstetrics and Gynecology, PCMS & RC Bhopal. 200 eligible postpartum women were counselled for IUCD insertion. After consent, Cu-T 380 A insertion was done. These women were also interviewed for their reasons for accepting and rejecting PPIUCD and their preference for other forms of contraception. Follow-up was done at 6 week or when they reported with any complaint. Results: Out of 200 eligible postpartum patient counselled, 72 (36%) women underwent PPIUCD insertion which was significantly low as compared to preference to use of other methods of contraception at a later date (66%). Acceptance of PPIUCD was higher in the age group of 21-29 years (35%), para-1 (48%), and educated (60%) clients. Expulsion rate was 22%. There was no case of perforation or any other major complication. 52 cases (72%) reported for follow up. 43% of cases were comfortable with PPIUCD at 6 weeks. There was no case of perforation, PID reported in our study. Only one patient reported with intrauterine pregnancy at 6months with IUCD in place. Conclusions: PPIUCD was not very acceptable in our set up but it is a safe, highly effective, long acting, cost effective method of contraception with very few side effects and no major complication and contraindication. The feasibility of accepting PPIUCD insertion can increase with antenatal counselling and institutional deliveries.